The Role of Diffusion in Figure Hunt Games - Diebold, Julia; Tari, Sibel; Cremers, Daniel (Journal of Mathematical Imaging and Vision, 2015)
We consider the task of tracing out target figures hidden in teeming figure pictures known as figure hunt games. Figure hunt games are a popular genre of visual puzzles; a timeless classic for children, artists and cognitive scientists. We argue and experimentally demonstrate that diffusion is a key to algorithmically search for a target figure in a binary line drawing. Particularly suited to the considered task, we propose a diffuse representation which diffuses the image while retaining the contour information.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Applications of variational and PDE methods; Figure hunt games; Level sets; Non-linear diffusion; Screened Poisson PDE and variants; Teeming figure pictures